The Relationship Between Childhood Trauma and the Response to Group Cognitive-Behavioural Therapy for Chronic Fatigue Syndrome - De Venter, Maud; Illegems, Jela; Van Royen, Rita; Sabbe, Bernard G. C.; Moorkens, Greta; Van Den Eede, Filip (Frontiers in Psychiatry, 2020)
Objective: To examine the relationship between childhood trauma and the response to group cognitive-behavioural therapy (GCBT) for chronic fatigue syndrome (CFS). Methods: A single cohort study conducted in an outpatient university referral center for CFS including a well-documented sample of adult patients meeting the CDC criteria for CFS and having received 9 to 12 months of GCBT. A mixed effect model was adopted to examine the impact of childhood trauma on the treatment response in general and over time. The main outcome measures were changes in fatigue, as assessed with the Checklist Individual Strength (total score), and physical functioning, as gauged with the Short Form 36 Health Survey subscale, with the scales being completed at baseline, immediately after treatment completion and after one year. Results: We included 105 patients with CFS. Childhood trauma was not significantly associated with the response to GCBT over time on level of fatigue or physical functioning. Conclusion: Childhood trauma does not seem to have an effect on the treatment response to dedicated GCBT for CFS sufferers over time. Therefore, in the allocation of patients to this kind of treatment, a history of childhood trauma should not be seen as prohibitive.